2012
DOI: 10.1155/2012/568797
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Lead(II) and Organotin(IV) Complexes of Schiff Bases Derived from Histidine and Methionine

Abstract: New Schiff base (HL) ligand is prepared via condensation of isatins and amino acids in 1:1 molar ratio. Metal complexes are prepared and characterized by elemental analysis, molar conductance, electronic, infrared, and multinuclear magnetic resonance ( 1 H NMR, 13 C NMR, and 119 Sn NMR). The analytical data showed that the ligand acts as bidentate toward metal ions via azomethine nitrogen and carboxylate oxygen by a stoichiometric reaction of metal : ligand (1 : 2) to from metal complexes (Pb(II)(L) 2 and Bu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The (COO -) bands at 1541 cm -1 and 1390 cm -1 for asymmetric and symmetric stretching in ligands are shifted to 1496 cm -1 and 1311 cm -1 in complexes. A new band at 3404 cm -1 is ascertained in the spectra of complex only and is assigned to υ(H 2 O) [8,10,12].…”
Section: Infrared Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The (COO -) bands at 1541 cm -1 and 1390 cm -1 for asymmetric and symmetric stretching in ligands are shifted to 1496 cm -1 and 1311 cm -1 in complexes. A new band at 3404 cm -1 is ascertained in the spectra of complex only and is assigned to υ(H 2 O) [8,10,12].…”
Section: Infrared Studiesmentioning
confidence: 99%
“…The tin ion has vacant 5d orbital and consequently ligand-to-metal (L→M) binding can take place by the acceptance of pair of electrons from ligand to the tin metal. No d-d transition is expected for tin complexes [8,12,15,17,26,27]. …”
Section: Electronic Absorption Spectral Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandhu and Verma in their studies and reports have shown that the Δ value of complexes greater by 65-90 cm −1 than in their sodium salts indicates either asymmetric or monodentate bonding of the carboxylate group to metal atom [32]. Moreover, Δ values of complexes below 200 cm −1 would be expected for bridging or chelating carboxylates, but greater than 200 cm −1 for the monodentate bonding carboxylate anions [33]. The C=O band of the indole group appears in the range of 1720-1740 cm −1 in the ligands.…”
Section: Ir Spectramentioning
confidence: 91%
“…It can be seen that the results for the Pb(II) ions loaded sample were almost same as the pre-adsorption sample, However, some of the bands after lead ions were loaded shifted to a lower value than that of the pre-adsorption sample, confirming the adsorption of the Pb(II) ions on the silica surface. This suggests the involvement of the oxygen atom of the carboxylate anion with the azomethine nitrogen and the Pb(II) ion [35]. The infrared spectrum in Figure 2b revealed the asymmetric stretching vibration of ν as (COO − ) of adsorbent 1 at 1665 cm −1 was shifted to a lower wave number (1642 cm −1 ) after the Pb(II) ion was loaded, indicating that the lead ion coordination took place via the oxygen atom of the carboxylate anion [36].…”
Section: The Ft-ir Spectra Of Adsorbent 1 Before and After Loading Pbmentioning
confidence: 99%